2016
DOI: 10.2967/jnumed.116.181826
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Somatic Mutations and Metabolic Imaging Phenotypes in Non–Small Cell Lung Cancer

Abstract: PET-based radiomics have been used to noninvasively quantify the metabolic tumor phenotypes; however, little is known about the relationship between these phenotypes and underlying somatic mutations. This study assessed the association and predictive power of 18 F-FDG PET-based radiomic features for somatic mutations in non-small cell lung cancer patients. Methods: Three hundred forty-eight non-small cell lung cancer patients underwent diagnostic 18 F-FDG PET scans and were tested for genetic mutations. Thirte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
105
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 140 publications
(114 citation statements)
references
References 50 publications
7
105
0
2
Order By: Relevance
“…In addition to EGFR mutation prediction based on CT images, EGFR mutations were predicted based on Positron Emission Computed Tomography (PET)/CT. Notably, Yip et al performed radiomics analysis of PET images and identified significant features for distinguishing EGFR mutation status . However, these studies were designed to predict the overall mutation status of EGFR, and did not specifically describe the relevant radiomic features associated with EGFR mutation subtypes.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to EGFR mutation prediction based on CT images, EGFR mutations were predicted based on Positron Emission Computed Tomography (PET)/CT. Notably, Yip et al performed radiomics analysis of PET images and identified significant features for distinguishing EGFR mutation status . However, these studies were designed to predict the overall mutation status of EGFR, and did not specifically describe the relevant radiomic features associated with EGFR mutation subtypes.…”
Section: Discussionmentioning
confidence: 99%
“…Given that somatic mutations affect the ability of cells to grow in otherwise non-permissive conditions, we decided to test whether these conditions can be quantified by radiomics and if they reflect the underlying mutational landscape - and whether one could use radiomic phenotype to predict tumor genotype. Although, associations between diagnostic imaging features and mutational data have been explored (2434), most studies suffer from small cohort sizes, do not include external validation, or have relied on observer-dependent semi-quantitative features that make replication difficult. We hypothesized that automated quantitative radiomic feature extraction, applied to a large, heterogeneous cohort, and rigorously validated, could establish the genotype-imaging phenotype linkage.…”
Section: Introductionmentioning
confidence: 99%
“…Radiomics, that encodes tumor phenotypes with innumerable quantitative features using predefined image analysis algorithms. In particular, previous studies have demonstrated that certain radiomic features are associated with EGFR mutations status, suggesting that those identified features may be driven by somatic mutations . Although these studies have achieved impressive performances, especially when combined with clinical information, conventional radiomics‐based methods are born with three main challenges.…”
Section: Introductionmentioning
confidence: 99%